Magnesium-based composite material with titanium-zirconium cladding structure interface and preparation method of magnesium-based composite material

By generating the titanium-zirconium clad structural interface in situ in magnesium-based composites, the problem of uneven distribution of the interface between titanium and magnesium matrix is ​​solved, and the mechanical properties of the material are significantly improved, including yield strength, tensile strength and elongation.

CN119265466APending Publication Date: 2025-01-07CHONGQING UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411380922.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The interfacial product distribution between titanium and magnesium matrix in existing titanium/magnesium matrix composite materials is uneven, which makes it difficult for the reinforcement to effectively transfer loads, limiting the comprehensive mechanical properties of the material.

Method used

By in situ generating a titanium-zirconium clad structure interface in magnesium-based composite materials, using Ti particles as core structure and ZrTi layer as shell structure, uniformly dispersed in magnesium alloy, optimizing process conditions such as heating and stirring processes to form uniform titanium-zirconium Covered structure.

Benefits of technology

The bonding strength between Ti particles and magnesium matrix is ​​significantly improved, the uniform dispersion of Ti particles is promoted, the problem of interface cracking is overcome, the yield strength, tensile strength and elongation of magnesium-based composite materials are improved, and the comprehensive mechanical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265466A_ABST
    Figure CN119265466A_ABST
Patent Text Reader

Abstract

The invention relates to a magnesium-based composite material with a titanium-zirconium cladding structure interface and a preparation method of the magnesium-based composite material, and belongs to the technical field of magnesium alloy materials. The magnesium-based composite material comprises a magnesium alloy and a reinforcement which is uniformly dispersed in the magnesium alloy, takes Ti particles as a core and takes a ZrTi layer as a shell and has a core-shell structure. In the process of preparing the magnesium-based composite material, by optimizing the mass ratio of all the components in the magnesium-based composite material and preparation process conditions, a cladding structure interface can be generated in situ in the casting process of Ti particles and a magnesium matrix, and by means of the interface, the interface bonding strength of the interface of the Ti particles and the magnesium matrix can be remarkably improved; the magnesium-based composite material prepared by the preparation method disclosed by the invention has the advantages of high mechanical property and high mechanical property, can promote uniform dispersion of Ti particles in a magnesium matrix, overcomes the problems of easy interface cracking and debonding of a reinforcement body in a traditional composite material, effectively improves the reinforcement effect of the Ti particles in the magnesium matrix, and finally improves the comprehensive mechanical property of the magnesium-based composite material. In addition, the technological process is simple, controllability is high, the method is suitable for large-scale industrial production, and remarkable economic benefits and application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy materials, and relates to a magnesium-based composite material with a titanium-zirconium cladding structure interface and a preparation method thereof. Background Art

[0002] Magnesium is the lightest structural metal with a density of only 1.74g / cm 3 , which is about 2 / 3 of aluminum. Magnesium alloys have the advantages of high specific strength, high specific stiffness, good damping coefficient, good dimensional stability, strong electromagnetic shielding capability and easy recycling. In recent years, in order to further improve the mechanical properties of magnesium alloys, researchers have extensively explored the introduction of various reinforcement schemes. Among them, titanium particles, as a high-strength, corrosion-resistant metal material, have gradually become a widely-regarded reinforcement in magnesium-based composites due to their good compatibility with the magnesium alloy matrix and potential reinforcement effect. Titanium particles can significantly improve the comprehensive mechanical properties of composites by forming a composite structure with the magnesium matrix, especially in improving their strength and plasticity.

[0003] However, in the existing titanium / magnesium-based composite material preparation process, the interface products between titanium and magnesium matrix are usually clustered nano-TiAl particles, TiMn particles and some oxide particles, which are unevenly distributed and difficult to control in size, easily leading to local stress concentration, making it difficult for the reinforcement to effectively transfer the load, thus limiting its reinforcement effect. How to ensure the formation of a strong interface between titanium particles and magnesium matrix during the preparation process, and how to optimize the microstructure of the composite material to improve its comprehensive performance have become an important challenge in this field of research. Summary of the invention

[0004] In view of this, one of the objects of the present invention is to provide a magnesium-based composite material having a titanium-zirconium cladding structure interface; a second object is to provide a method for preparing a magnesium-based composite material having a titanium-zirconium cladding structure interface.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] 1. A magnesium-based composite material with a titanium-zirconium cladding structure interface, the magnesium-based composite material comprising a magnesium alloy and a reinforcement uniformly dispersed in the magnesium alloy, the reinforcement comprising a core structure located at the center and a shell structure covering the core structure, the core structure being Ti particles, and the shell structure being a ZrTi layer.

[0007] Preferably, the average particle size of the Ti particles is ≤10 μm.

[0008] Preferably, the thickness of the ZrTi layer is 2-5 μm.

[0009] Preferably, the magnesium-based composite material comprises the following components by mass percentage: 3-10wt.% of Ti particles, and the balance is Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy;

[0010] The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 5-10wt.% Gd, 2-5wt.% Y, 0.1-0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance Mg;

[0011] The Mg-Gd-Y-Zn-Zr alloy is composed of the following components by mass percentage: 5-10wt.% Gd, 2-5wt.% Y, 0.01-2wt.% Zn, 0.1-0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance Mg.

[0012] 2. A method for preparing a magnesium-based composite material having a titanium-zirconium cladding structure interface, the method being as follows:

[0013] The Mg-Gd-Y-Zr alloy or the Mg-Gd-Y-Zn-Zr alloy is heated and melted to obtain a slurry; the slurry is continuously stirred for 5-10 minutes and then cooled to 620-640°C, preheated Ti particles are added, and stirring is continued for 10-30 minutes, and then stirring is continued until the temperature rises to 660-680°C and then the stirring is stopped, and an ingot is obtained after casting; the ingot is homogenized and then extruded into a shape.

[0014] Preferably, the method is as follows:

[0015] The Mg-Gd-Y-Zr alloy or the Mg-Gd-Y-Zn-Zr alloy is heated and melted to obtain a slurry; the slurry is continuously stirred at a rotation speed of 150-200 rpm for 5-10 minutes, then cooled to 620-640°C, preheated Ti particles are added, and the slurry is continuously stirred at a rotation speed of 400-500 rpm for 10-30 minutes, and then the stirring is continuously stirred at a rotation speed of 100-200 rpm until the temperature rises to 660-680°C, and then the stirring is stopped, and an ingot is obtained after casting; the ingot is homogenized and then extruded to form.

[0016] Preferably, the heating power is reduced to 0-5%, and the temperature is reduced to 620-640°C; the heating power is increased to 15-25%, and the temperature is increased to 660-680°C.

[0017] Preferably, the Mg-Gd-Y-Zr alloy or the Mg-Gd-Y-Zn-Zr alloy is heated and melted as follows:

[0018] The Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy is placed in a casting furnace and vacuumed to 1×10 -1 After reaching Pa, the valve is closed, the temperature is first raised to 600-630° C. at a heating power of 15-25%, and then raised to 670-700° C. at a heating power of 5-10%, and the temperature is maintained until the Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy is completely melted.

[0019] Preferably, the homogenization treatment is specifically: solutionizing the ingot at 500-540° C. for 8-24 hours.

[0020] Preferably, the extrusion molding is specifically as follows: the homogenized ingot is kept at 450-500°C for 0.5-1h, the extrusion die is preheated to 400-450°C, and then hot extrusion is performed at an extrusion rate of 0.5-3mm / s and an extrusion ratio of 16-25:1.

[0021] The beneficial effects of the present invention are as follows: the present invention provides a magnesium-based composite material having a titanium-zirconium cladding structure interface and a preparation method thereof, by optimizing the mass ratio of each component in the magnesium-based composite material and the preparation process conditions, the Ti particles and the magnesium matrix can generate a cladding structure interface in situ during the casting process, specifically as follows Figure 1 As shown, Zr solute atoms are distributed around Ti particles, and Zr solute atoms gather at the interface between Ti particles and magnesium matrix, and finally form a reinforcement with a core-shell structure with Ti particles as the core and ZrTi layer as the shell, and the reinforcement can be evenly dispersed in the magnesium alloy. The titanium zirconium cladding structure interface can not only significantly improve the interface bonding strength between Ti particles and magnesium matrix, optimize the microstructure of the composite material, but also promote the uniform dispersion of Ti particles in the magnesium matrix, thereby effectively transferring the load, overcoming the problem that the reinforcement in the traditional composite material is prone to interface cracking and causing debonding, and effectively improving the reinforcement effect of Ti particles in the magnesium matrix, thereby ultimately improving the yield strength, tensile strength and elongation of the magnesium-based composite material. Among them, the yield strength of the magnesium-based composite material in the present invention is 180-300MPa, the tensile strength is 300-400MPa, and the elongation is 15-30%. In addition, the process flow of the present invention is simple, controllable, suitable for large-scale industrial production, and has significant economic benefits and application prospects.

[0022] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0024] Figure 1 It is a schematic diagram of the interface of the titanium-zirconium cladding structure formed in situ in the magnesium matrix in the present invention;

[0025] Figure 2 This is a distribution diagram of SEM-EDS surface scanning results of the magnesium-based composite material with titanium-zirconium cladding structure interface prepared in Example 1 of the present invention;

[0026] Figure 3 This is a distribution diagram of the SEM-EDS surface scanning results of the magnesium-based composite material with a titanium-zirconium cladding structure interface prepared in Example 7 of the present invention;

[0027] Figure 4 This is a distribution diagram of the SEM-EDS surface scanning results of the magnesium-based composite material with a titanium-zirconium cladding structure interface prepared in Comparative Example 1 of the present invention;

[0028] Figure 5 This is a distribution diagram of the SEM-EDS surface scanning results of the magnesium-based composite material with a titanium-zirconium cladding structure interface prepared in Comparative Example 2 of the present invention;

[0029] Figure 6 This is a TKD-EDS image of the titanium-zirconium cladding structure interface in the magnesium-based composite material with a titanium-zirconium cladding structure interface prepared in Example 1. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0031] Example 1

[0032] Preparation of magnesium-based composites with titanium-zirconium cladding structure interface

[0033] S1. Ingredients by mass percentage: 3wt.% of TA1 titanium alloy spherical powder with an average particle size of ≤10μm, and the balance is Mg-Gd-Y-Zr alloy. The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 9wt.% Gd, 3wt.% Y, 0.5wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0034] S2. Ingot preparation: Mg-Gd-Y-Zr alloy is placed in a vacuum stirring casting furnace and vacuumed to 1×10 -1 After Pa, close the valve and start induction heating. First, heat it to 600°C at a heating rate of 15°C / min and a heating power of 20%, then heat it to 680°C at a heating rate of 10°C / min and a heating power of 5%, and keep warm until the Mg-Gd-Y-Zr alloy is completely melted to obtain alloy slurry; turn on the agitator and stir the alloy slurry continuously at a speed of 150 rpm for 5 minutes, then reduce the heating power to 5%, cool it to 630°C, add preheated TA1 titanium alloy spherical powder, stir it at a speed of 450 rpm for 25 minutes, then increase the heating power to 20%, stir it at a speed of 150 rpm until the temperature rises to 675°C, and then stop stirring.

[0035] S3. Homogenization treatment: The ingot obtained in step S2 is solutionized at 520° C. for 12 h.

[0036] S4. Extrusion molding: The ingot after homogenization treatment is kept at 500°C for 1 hour, the extrusion die is preheated to 420°C, and then hot extrusion is carried out at an extrusion rate of 1.5 mm / s and an extrusion ratio of 25:1 to obtain a magnesium-based composite material with a titanium-zirconium cladding structure interface.

[0037] Example 2

[0038] Preparation of magnesium-based composites with titanium-zirconium cladding structure interface

[0039] S1. Ingredients by mass percentage: 10wt.% of TA1 titanium alloy spherical powder with an average particle size of ≤10μm, and the balance is Mg-Gd-Y-Zr alloy. The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 9wt.% Gd, 4wt.% Y, 0.5wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0040] S2. Ingot preparation: Mg-Gd-Y-Zr alloy is placed in a vacuum stirring casting furnace and vacuumed to 1×10 -1After Pa, close the valve and start induction heating. First, heat it to 610°C at a heating rate of 20°C / min and a heating power of 25%, then heat it to 700°C at a heating rate of 5°C / min and a heating power of 5%, and keep warm until the Mg-Gd-Y-Zr alloy is completely melted to obtain alloy slurry; turn on the agitator and stir the alloy slurry continuously at a speed of 200 rpm for 10 minutes, then reduce the heating power to 5%, cool it to 635°C, add the preheated TA1 titanium alloy spherical powder, stir it at a speed of 500 rpm for 30 minutes, then increase the heating power to 20%, stir it at a speed of 100 rpm until the temperature reaches 680°C, and then stop stirring.

[0041] S3. Homogenization treatment: The ingot obtained in step S2 is solutionized at 540° C. for 12 h.

[0042] S4. Extrusion molding: The ingot after homogenization treatment is kept at 500°C for 1 hour, the extrusion die is preheated to 420°C, and then hot extrusion is carried out at an extrusion rate of 1.5 mm / s and an extrusion ratio of 25:1 to obtain a magnesium-based composite material with a titanium-zirconium cladding structure interface.

[0043] Example 3

[0044] Preparation of magnesium-based composites with titanium-zirconium cladding structure interface

[0045] S1. Ingredients by mass percentage: 5wt.% of TA1 titanium alloy spherical powder with an average particle size of ≤10μm, and the remainder is Mg-Gd-Y-Zr alloy. The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 7wt.% Gd, 5wt.% Y, 0.1wt.% Zr, unavoidable impurities ≤0.25wt.%, and the remainder is Mg.

[0046] S2. Ingot preparation: Mg-Gd-Y-Zr alloy is placed in a vacuum stirring casting furnace and vacuumed to 1×10 -1 After Pa, close the valve and start induction heating. First, heat it to 620°C at a heating rate of 30°C / min and a heating power of 15%, then heat it to 670°C at a heating rate of 15°C / min and a heating power of 7%, and keep it warm until the Mg-Gd-Y-Zr alloy is completely melted to obtain alloy slurry; turn on the agitator and stir the alloy slurry continuously at a speed of 150 rpm for 8 minutes, then reduce the heating power to 3%, cool it to 640°C, add the preheated TA1 titanium alloy spherical powder, stir it at a speed of 400 rpm for 20 minutes, then increase the heating power to 25%, stir it at a speed of 150 rpm until the temperature rises to 665°C, and then stop stirring.

[0047] S3. Homogenization treatment: The ingot obtained in step S2 is solutionized at 540° C. for 8 h.

[0048] S4. Extrusion molding: The ingot after homogenization treatment is kept at 475°C for 0.5h, the extrusion die is preheated to 400°C, and then hot extrusion is performed at an extrusion rate of 0.5mm / s and an extrusion ratio of 20:1 to obtain a magnesium-based composite material with a titanium-zirconium cladding structure interface.

[0049] Example 4

[0050] Preparation of magnesium-based composites with titanium-zirconium cladding structure interface

[0051] S1. Ingredients by mass percentage: 8wt.% of TA1 titanium alloy spherical powder with an average particle size of ≤10μm, and the remainder is Mg-Gd-Y-Zr alloy. The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 5wt.% Gd, 2wt.% Y, 0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the remainder is Mg.

[0052] S2. Ingot preparation: Mg-Gd-Y-Zr alloy is placed in a vacuum stirring casting furnace and vacuumed to 1×10 -1 After Pa, close the valve and start induction heating. First, heat it to 630°C at a heating rate of 10°C / min and a heating power of 20%, then heat it to 680°C at a heating rate of 10°C / min and a heating power of 10%, and keep it warm until the Mg-Gd-Y-Zr alloy is completely melted to obtain alloy slurry; turn on the agitator and stir the alloy slurry continuously at a speed of 200 rpm for 5 minutes, then reduce the heating power to 2%, cool it to 620°C, add the preheated TA1 titanium alloy spherical powder, stir it continuously at a speed of 475 rpm for 10 minutes, then increase the heating power to 15%, stir it continuously at a speed of 200 rpm until the temperature reaches 660°C, and then stop stirring.

[0053] S3. Homogenization treatment: subjecting the ingot obtained in step S2 to solid solution treatment at 500° C. for 24 hours.

[0054] S4. Extrusion molding: The ingot after homogenization treatment is kept at 450°C for 0.5h, the extrusion die is preheated to 450°C, and then hot extrusion is performed at an extrusion rate of 3mm / s and an extrusion ratio of 16:1 to obtain a magnesium-based composite material with a titanium-zirconium cladding structure interface.

[0055] Example 5

[0056] The difference from Example 1 is that the ingredients are prepared by mass percentage: 10 wt.% of TA1 titanium alloy spherical powder with an average particle size of ≤10 μm.

[0057] Example 6

[0058] The difference from Example 1 is that the Mg-Gd-Y-Zr alloy is replaced by a Mg-Gd-Y-Zn-Zr alloy, which is composed of the following components in mass percentage: 9wt.% Gd, 3wt.% Y, 0.1wt.% Zn, 0.5wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0059] Example 7

[0060] The difference from Example 2 is that the Mg-Gd-Y-Zr alloy is replaced by a Mg-Gd-Y-Zn-Zr alloy, which is composed of the following components in mass percentage: 9wt.% Gd, 4wt.% Y, 0.8wt.% Zn, 0.5wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0061] Example 8

[0062] The difference from Example 3 is that the Mg-Gd-Y-Zr alloy is replaced by a Mg-Gd-Y-Zn-Zr alloy, which is composed of the following components in mass percentage: 7wt.% Gd, 5wt.% Y, 2wt.% Zn, 0.1wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0063] Example 9

[0064] The difference from Example 4 is that the Mg-Gd-Y-Zr alloy is replaced by a Mg-Gd-Y-Zn-Zr alloy, which is composed of the following components in mass percentage: 5wt.% Gd, 2wt.% Y, 1.5wt.% Zn, 0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that the Mg-Gd-Y-Zr alloy is replaced by a Mg-Gd-Y-Mn alloy, which is composed of the following components by mass percentage: 9wt.% Gd, 3wt.% Y, 0.5wt.% Mn, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0067] Comparative Example 2

[0068] The difference from Example 7 is that the Mg-Gd-Y-Zn-Zr alloy is replaced by a Mg-Gd-Y-Zn-Mn alloy, which is composed of the following components in mass percentage: 9wt.% Gd, 4wt.% Y, 0.8wt.% Zn, 0.5wt.% Mn, unavoidable impurities ≤0.25wt.%, and the balance is Mg.

[0069] The magnesium-based composite materials with titanium-zirconium cladding structure interface prepared in Example 1, Example 7 and Comparative Example 1 and Comparative Example 2 were characterized by SEM-EDS electron microscope, and the results were as follows: Figure 2-5 As shown by Figure 2 and Figure 3 It can be seen that the Zr element in the magnesium-based composite material in Example 1 and Example 7 is enriched around the spherical particles of the TA1 titanium alloy, forming an obvious ring structure, indicating that the Zr element and the Ti element diffuse with each other to form an interface product, namely, a ZrTi layer, at the Ti-Mg interface. Figure 4 and Figure 5 It can be seen that the Mn element in the magnesium-based composite materials in Comparative Examples 1 and 2 is not enriched around the TA1 titanium alloy spherical particles, and no ring structure is formed, indicating that after replacing the elements, an in-situ cladding structure interface cannot be obtained in the composite material.

[0070] The titanium-zirconium cladding structure interface in the magnesium-based composite material with a titanium-zirconium cladding structure interface prepared in Example 1 was characterized using a TKD-EDS electron microscope. The results are as follows: Figure 6 As shown by Figure 6 It can be seen that the thickness of the in-situ titanium-zirconium cladding structure interface (i.e., ZrTi layer) in the magnesium-based composite material is 2μm. The sheet-like structure ZrTi phase on the interface is different from the equiaxial grain shape of Mg and Ti, and its size is smaller, which can ensure that the magnesium-based composite material has higher strength. At the same time, it was found that there were no obvious cracks, debonding and other defects at the titanium-zirconium cladding structure interface, indicating that the in-situ generation of the titanium-zirconium cladding structure interface will significantly improve the bonding strength between the TA1 titanium alloy spherical particles and the Mg matrix, so as to further improve the comprehensive mechanical properties of the composite material.

[0071] The mechanical properties of the magnesium-based composite materials with titanium-zirconium cladding structure interfaces prepared in Example 1, Example 5, Example 7 and Comparative Example 1 and Comparative Example 2 were tested respectively. The test results are shown in Table 1.

[0072] Table 1

[0073]

[0074] It can be seen from Table 1 that the comprehensive mechanical properties of the magnesium-based composite materials with titanium-zirconium cladding structure interface prepared in Example 1, Example 5 and Example 7 are better than the comprehensive mechanical properties of the magnesium-based composite materials without titanium-zirconium cladding structure interface prepared in Comparative Examples 1-2, among which the elongation is most significantly improved.

[0075] Compared with the magnesium-based composite material without titanium-zirconium cladding structure interface prepared in Comparative Examples 1-2, the present invention generates a titanium-zirconium cladding structure interface by in-situ reaction of TA1 titanium alloy spherical particles with solute atoms Zr. This interface significantly enhances the load transfer efficiency of the TA1 titanium alloy spherical particles in the magnesium-based composite material, greatly improves the overall strength of the magnesium-based composite material, and at the same time ensures the plasticity of the magnesium-based composite material, so that it has more excellent comprehensive mechanical properties.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A magnesium-based composite material having a titanium-zirconium cladding structure interface, characterized in that: The magnesium-based composite material comprises a magnesium alloy and a reinforcement uniformly dispersed in the magnesium alloy, wherein the reinforcement comprises a core structure located at the center and a shell structure covering the core structure, wherein the core structure is a Ti particle and the shell structure is a ZrTi layer.

2. A magnesium-based composite material having a titanium-zirconium cladding structure interface as claimed in claim 1, characterized in that: The average particle size of the Ti particles is ≤10 μm.

3. A magnesium-based composite material having a titanium-zirconium cladding structure interface as claimed in claim 1, characterized in that: The thickness of the ZrTi layer is 2-5 μm.

4. A magnesium-based composite material having a titanium-zirconium cladding structure interface according to any one of claims 1 to 3, characterized in that: The magnesium-based composite material comprises the following components by mass percentage: 3-10wt.% of Ti particles, and the balance is Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy; The Mg-Gd-Y-Zr alloy is composed of the following components by mass percentage: 5-10wt.% Gd, 2-5wt.% Y, 0.1-0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance Mg; The Mg-Gd-Y-Zn-Zr alloy is composed of the following components by mass percentage: 5-10wt.% Gd, 2-5wt.% Y, 0.01-2wt.% Zn, 0.1-0.8wt.% Zr, unavoidable impurities ≤0.25wt.%, and the balance Mg.

5. The method for preparing a magnesium-based composite material having a titanium-zirconium cladding structure interface as claimed in claim 4, characterized in that: The method is as follows: The Mg-Gd-Y-Zr alloy or the Mg-Gd-Y-Zn-Zr alloy is heated and melted to obtain a slurry; the slurry is continuously stirred for 5-10 minutes and then cooled to 620-640°C, preheated Ti particles are added, and stirring is continued for 10-30 minutes, and then stirring is continued until the temperature rises to 660-680°C and then the stirring is stopped, and an ingot is obtained after casting; the ingot is homogenized and then extruded into a shape.

6. The preparation method according to claim 5, characterized in that: The method is as follows: The Mg-Gd-Y-Zr alloy or the Mg-Gd-Y-Zn-Zr alloy is heated and melted to obtain a slurry; the slurry is continuously stirred at a rotation speed of 150-200 rpm for 5-10 minutes, then cooled to 620-640°C, preheated Ti particles are added, and the slurry is continuously stirred at a rotation speed of 400-500 rpm for 10-30 minutes, and then the stirring is continuously stirred at a rotation speed of 100-200 rpm until the temperature rises to 660-680°C, and then the stirring is stopped, and an ingot is obtained after casting; the ingot is homogenized and then extruded to form.

7. The preparation method according to claim 5 or 6, characterized in that: Reduce the heating power to 0-5% and the temperature to 620-640℃; increase the heating power to 15-25% and the temperature to 660-680℃.

8. The preparation method according to claim 5 or 6, characterized in that: The Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy is heated and melted as follows: The Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy is placed in a casting furnace and vacuumed to 1×10 -1 After reaching Pa, the valve is closed, the temperature is first raised to 600-630° C. at a heating power of 15-25%, and then raised to 670-700° C. at a heating power of 5-10%, and the temperature is maintained until the Mg-Gd-Y-Zr alloy or Mg-Gd-Y-Zn-Zr alloy is completely melted.

9. The preparation method according to claim 5 or 6, characterized in that: The homogenization treatment is specifically as follows: solutionizing the ingot at 500-540° C. for 8-24 hours.

10. The preparation method according to claim 5 or 6, characterized in that: The extrusion molding is specifically as follows: the homogenized ingot is kept at 450-500°C for 0.5-1h, the extrusion die is preheated to 400-450°C, and then hot extrusion is performed at an extrusion rate of 0.5-3mm / s and an extrusion ratio of 16-25:1.

Citation Information

Patent Citations

  • High-strength high-plasticity magnesium-based composite material and preparation method thereof

    CN112342445A

  • Titanium particle reinforced magnesium-based composite material and preparation method thereof

    CN114959391A

  • Preparation method of micron-sized titanium particle reinforced magnesium-based composite material

    CN115852181A

  • Preparation method of titanium alloy particle reinforced rare earth magnesium-based composite material and product

    CN116770142A

  • Titanium particle reinforced magnesium-based composite material as well as preparation method and application thereof

    CN117165822A